THE ROLE OF INTERNATIONAL FINANCIAL INSTITUTIONS IN SUPPORTING ECONOMIC REFORMS AND INVESTMENT ATTRACTIVENESS IN UZBEKISTAN - Khamzaeva Visola Khamzaevna (American Journals, 2026)
This study examines the role of international financial institutions (IFIs), including the International Monetary Fund, World Bank, and Asian Development Bank, in supporting economic reforms and improving investment attractiveness in Uzbekistan during 2015–2024. The research applies quantitative analysis of macroeconomic indicators and qualitative assessment of IFI-supported development projects. The findings show that IFI cooperation contributed to GDP growth, increased foreign direct investment, and strengthened financial sector stability. Despite positive progress, challenges such as administrative barriers and regional disparities remain. The study concludes that continued cooperation with IFIs is essential for sustainable economic development and long-term investment growth in Uzbekistan.
Keywords: International financial institutions, economic reforms, foreign direct investment, investment attractiveness, financial sector development, economic growth, Uzbekistan.